2016
DOI: 10.1002/adma.201603880
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Efficient and Self‐Stabilizing Metallic‐Glass Catalyst for Electrochemical Hydrogen Generation

Abstract: A multicomponent metallic glass (MG) with highly efficient and anomalous durability for catalyzing water splitting is reported. The outstanding performance of the MG catalyst contributed by self-optimized active sites originates from the intrinsic chemical heterogeneity and selective dealloying on the disordered surface; thus, a new mechanism for improving the durability of catalysts is uncovered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
86
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(104 citation statements)
references
References 39 publications
3
86
0
Order By: Relevance
“…The surface of amorphous alloy has more unsaturated coordination, which can provide more active sites for chemical reactions. With theoretical calculations, Hu [34] pointed out that the bonding mechanism of atoms in amorphous structure was different from the case in crystalline structure. The excellent catalytic activity of amorphous electrodes resulted from the abundance of the active sites induced by the special electronic structure.…”
Section: Resultsmentioning
confidence: 99%
“…The surface of amorphous alloy has more unsaturated coordination, which can provide more active sites for chemical reactions. With theoretical calculations, Hu [34] pointed out that the bonding mechanism of atoms in amorphous structure was different from the case in crystalline structure. The excellent catalytic activity of amorphous electrodes resulted from the abundance of the active sites induced by the special electronic structure.…”
Section: Resultsmentioning
confidence: 99%
“…[18,19] To date, numerous nanoporous materials, especially nanoporous transition metals and their oxides, have been reported for efficient catalysts toward HER in alkaline electrolyte. [26][27][28][29] Nevertheless, the HER properties of these MG electrocatalysts are mostly determined in acid, and the low surface area of MG ribbons also limits their electrocatalytic activity. More recently, metallic glass (MG) ribbons with good mechanical flexibility have been suggested to be active electrocatalysts for HER due to their metastable state and richness of low-coordination sites at the surface.…”
Section: Doi: 101002/adma201904989mentioning
confidence: 99%
“…Many excellent research outcomes have demonstrated that MGs with several intrinsic catalytic advantages, such as widely tunable atomic components accompanied by fine tuning of electronic properties to satisfy catalytic selectivity demands, homogeneous and isotropic characteristics affording abundant catalytic active sites, the high density of unsaturated atomic coordination offering superior catalytic performance, etc., present great potential in practical catalytic applications. For example, recent reports have demonstrated that Pd–Ni–Cu–P MGs with intrinsic chemical heterogeneity and a selective dealloying function present a highly efficient and self‐optimized behavior for the hydrogen evolution reaction . Pt–Ni–Cu and Pt–Ni–Cu–P MGs, with precise regulation of surface elemental composition, exhibit highly active and durable performance in various catalytic applications.…”
Section: Introductionmentioning
confidence: 99%